Multi-walled carbon nanotube supported manganese selenide as a highly active bifunctional OER and ORR electrocatalyst. Issue 12 (24th February 2022) - Singh, Harish; Marley-Hines, McKenzie; Chakravarty, Shatadru; Nath, Manashi
Abstract : A manganese selenide and multiwalled carbon nanotube-based composite shows promising bifunctional electrocatalytic activity for the oxygen evolution and oxygen reduction reactions with superior stability and lower overpotential for both OER and ORR. Abstract : Transition metal selenides have attracted intensive interest as cost-effective electrocatalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) because of the continuous thrust in sustainable energy conversion. In this article a Mn-based bifunctional electrocatalyst, MnSe, has been identified which shows efficient OER and ORR activity in alkaline medium. The catalytic activity could be further enhanced by using multiwalled carbon nanotubes (MWCNTs) which increases the charge transfer and electronic conductivity of the catalyst composite. This MnSe@MWCNT catalyst composite exhibits a very low overpotential of 290 mV at 10 mA cm −2, which outperforms state-of-the-art RuO2 as well as other oxide based electrocatalysts. Furthermore, the composite's facile OER kinetics was evidenced by its small Tafel slope of 54.76 mV dec −1 and low charge transfer resistance, indicating quick transport of the reactant species at the electrode interface. The MnSe@MWCNT also exhibited efficient electrocatalytic activity for ORR with an E onset of 0.94 V, which is among the best reported to date for chalcogenide based ORR electrocatalysts. More importantly, this MnSe-based ORR electrocatalyst exhibits high degree of methanol tolerance, showing no degradation of catalyst performance in the presence of copious quantities of methanol, thereby out-performing the state-of-the-art Pt electrocatalyst. The catalyst composite also exhibited exceptional functional and compositional stability for OER and ORR after a prolonged period of continuous operation in alkaline medium. The surface Raman analysis after OER revealed the retention of manganese selenide surface with evidence of oxo coordination, confirming the formation of an (oxy)selenide as the active surface for OER. Such efficient bifunctional OER and ORR activity makes this MnSe based catalyst attractive for overall electrolysis in regenerative as well as direct methanol fuel cells.